Localised administration of chitosan hydrogel as periodontal regenerative therapy : Pemberian hidrogel kitosan secara lokal sebagai terapi regeneratif periodontal - Nggili, Joyce Srinovita; Djais, Arni Irawaty (Makassar Dental Journal, 2024)
One of the signs of periodontitis is the occurrence of infrabony defects. Chitosan is a natural-based polymer hydrogel that has bio-degradability, biocompatibility, bacteriostatic, non-toxic properties and has haemostatic and mucoadhesive capacities that are very beneficial in the periodontal regenerative process in periodontitis patients with infrabony defects. This systematic review dis-cusses the effectiveness of local application of chitosan hydrogels as periodontal regenerative therapy through PubMed and Google Scholar online literature databases limited to human randomised control clinical studies, published in the last eight years, on periodontal probing depth (PPD) and clinical attachment level (CAL). The initial search yielded 385 abstracts, 4 studies met the inclusion criteria that addressed the effectiveness of chitosan-based natural hydrogels on periodontal regenerative in periodon-titis patients with infrabony defects using open flap debridement (OFD)+chitosan (Cs), OFD+low molecular chitosan, OFD+high molecular chitosan, OFD+chitosan+fucoidan, OFD+chitosan+bonegraft surgical procedures. All studies showed improved of PPD and CAL within six months post-baseline. It was concluded that all procedures were effective in reducing PPD and increasing CAL. The use of chitosan can be considered an important material for periodontal regenerative therapy in periodontitis patients with infrabony defects.